Analisis kesulitan belajar siswa pada materi perbandingan kelas VII SMPN 02 cililin - Dimyati, Hesti; Maya, Rippi (IKIP Siliwangi, 2023)
This study looks at how difficult it is for seventh grade students of junior high school in working on comparison problems in terms of gender. This study uses a descriptive method with a qualitative approach used for this study. 10 students consisting of 5 male students and 5 female students from SMPN 02 Cililin were used as research subjects. The instrument used in the study was five items in the form of descriptions. The results of student test scores based on comparison questions are used in collecting research data, with indicators 1) restating a concept 2) applying concepts or algorithms in problem solving, 3) using and utilizing and having certain procedures or operations, based on the conclusions from the research results that is, it was concluded that the ability of class VII male students of SMPN 02 Cililin in working on comparison questions was still weak compared to female students. Lack of enthusiasm in participating in learning, student attitudes in participating in learning because they are used to online school, so students do not really understand the material that has been delivered.